Parenting Patterns In Forming The Independence Of Autism Children (Case Study: SLB Autisma Mutiara Bangsa Padang) - Andieni Delia Nadila; Lusi Tania Agustin; M Hubbal Khair; Nurva Dillatul Vatin; Wisda Rahmadinur (Institut Agama Islam Sumatera Barat, 2024)
Autism is a disorder classified based on a specific set of behaviors related to social communication and the type of behavior that is restricted or repetitive. Because this limited and repetitive behavior makes children with autism experience difficulties in their daily lives, namely a lack of independent ability. This research aims to determine the parenting patterns used by parents who have children with autism as well as the inhibiting and encouraging factors experienced by parents in forming the independence of children with autism. This study uses a qualitative method. The research subjects were parents of children with autism whose independent abilities were quite good. Data collection uses observation, interviews and documentation methods. The results of the research show that the parenting style applied by the research subjects tends to be authoritative parenting. This is characterized by providing direction and guidance from parents. Parents also provide opportunities for children to develop and direct themselves to be more responsible with their behavior. This is proven by parents not immediately helping children when they experience difficulties but rather parents giving directions first. Parents provide rewards and punishment to develop independence in children. In addition, there is parental control that is not rigid and parents are consistent in working on independence for children with autism.